Jo MacDonald had a garden - Quattlebaum, Mary (Dawn Publications, 2012)
In this version of the classic song "Old MacDonald Had a Farm," the farmer's granddaughter plants a garden which provides a place for birds, insects, and other wild creatures to shelter and nest. Backmatter presents facts and activities related to this lively ecosystem.